KRAS mutational concordance between primary and metastatic colorectal adenocarcinoma - PALIOGIANNIS, PANAGIOTIS (D.A. Spandidos, 2014)
KRAS mutation analysis is commonly performed on tissue samples obtained from primary colorectal cancers (CRCs). The metastatic lesions of CRC are usually considered as qualitatively similar or even identical to the primary tumors. The aim of this study was to evaluate the spectrum and distribution of KRAS mutations in a large collection of CRCs, while also evaluating the concordance of primary and metastatic lesions among available paired specimens from the same patients. A total of 729 patients with histologically confirmed advanced CRC at the University Hospital and Local Health Unit (Sassari, Italy) were included. Clinical and pathological features were obtained from medical records and/or pathology reports. Formalin-fixed, paraffin-embedded tissue samples were used for mutation analysis. Genomic DNA was isolated using a standard protocol; the coding sequence and splice junctions of exons 2 and 3 in the KRAS gene were screened by direct automated sequencing. Overall, 219 (30%) KRAS mutations were found; 208 (30.1%) were identified in the 690 primary tumors and 11 (28.2%) in the 39 metastatic tissue samples. Among the 31 (4.3%) patients who had paired samples of primary CRC and synchronous or asynchronous metastases, 28 (90.3%) showed consistent mutation patterns between the primary tumors and metastatic lesions. In one case, an additive mutation (Q61L) was found in the metastatic tissue, while two other discrepant cases exhibited a different mutation distribution; Q61H in the primitive lesion and G13V in the metastatic lesion in one case, and a mutated primary tumor (Q61L) and wild-type metastasis in another case. The results of this study confirm that a high concordance exists between the results of KRAS mutation analysis performed in primitive and metastatic CRCs; independent subclones may be generated in a limited amount of patients.